STUDY TO MICROSTRUCTURE AND MECHANICAL PROPERTIES OF Mg-Zn-Fe-Cu-Co AS HIGH ENTROPY ALLOYS FOR URETERAL IMPLANT APPLICATION - Andi Mulya Ashari (Metalurgi, 2021)
Magnesium and its alloys are promising candidates for degradable materials with good biocompatibility. Alloys based on Mg-Zn-Fe-Cu-Co compositions were designed using the equiatomic method of high entropy alloy. This paper discusses the microstructure and mechanical properties of these new high entropy alloys. Pure Magnesium (60 µm), Zinc (45 µm), Fe (10 µm), Cu (63 µm), and Co (1 µm) powder were mixed and milled using a shaker mill at 700 rpm for the 1800s. The resulting milled powders were compacted and sintered at 300 MPa for 180s and 600 MPa for 120s. Sintering was performed at 700oC for 2 hours in a tube vacuum furnace at a 5 °C/min heating rate under a high purity argon atmosphere. Microstructural analyses and mechanical tests were performed based on the American standard of testing and measurement. The alloys were basically multiphase and crystalline. The 20Mg-20Zn-20Fe-20Cu-20Co alloy consisted of the HCP phase and cubic phase. The physical and mechanical properties of Mg-Zn-Fe-Cu-Co were affected by the magnesium content in the matrix alloys. The presence of pores indicated uncomplete compaction and sintering process. The alloys have a medium hardness of between 286.06 HV - 80.98 HV, while the densities of the alloys were relatively moderate in the range of 3.057 g.cm-3 to 1.71 g.cm-3. Solid solution and intermetallic precipitation strengthening were believed the primary strengthening mechanics of the alloys. It is concluded that high entropy is a promising method for the processing of Mg alloys. Alloy with a chemical composition of 20Mg-20Zn-20Fe-20Cu-20Co had optimal mechanical properties that meet the minimum requirements of high entropy alloys as candidates for ureteral implant applications.